Implementasi Fuzzy Logic pada Analisis Kepuasaan Mahasiswa Terhadap Pelayanan Administrasi STMIK AKBA Makassar - Vera Alviani (Jurnal Ilmu Komputer dan Desain Komunikasi Visual, 2020)
This study aims to analyze student satisfaction with administrative services at STMIK AKBA Makassar, and then implement a student satisfaction analysis system for administrative services using fuzzy logic. Fuzzy logic has been used in fields such as taxonomy, topology, linguistics, automata theory, control theory, psychology, pattern recognition, medicine, law, decision analysis, system theory and information retrieval. Testing is done in alpha using the black box and betha method, namely entering data into the forms provided, the items being tested are system logins, satisfaction analysis, news and information, service data, expectation data, messages and analysis. Based on the results of alpha and beta testing that have been done, it can be concluded that the application is running quite optimally. Keywords— MySql Database, Fuzzy Logic, Administration Services, Web Programming